Low-profile frequency-reconfigurable antenna for 5G applications - Ali Kadhum Abd; Jamal Mohammed Rasool (Universitas Ahmad Dahlan, 2023)
The demand for higher data rates has increased in recent years. The reconfigurable antenna that operates in the millimeter-wave spectrum (23.5 GHz – 29.64 GHz) was developed. This design is obtained by merging a half-circle radius of 3.97 mm, and a half-ring inner radius of 4 mm. The shape is similar to the round bottom flask. Two PIN diodes are used in this design to achieve frequency reconfigurability to meet the wideband mobile communication need of the future 5G. The suggested antenna, built on Roger RT5880 substrates and properties of ε = 2.2 and δ = 0.0009, has been used as the antenna substrate. For all the resonant bands, the suggested antenna has a voltage standing waves ratio (VSWR) < 1.11. From 84 % to 92 %, the suggested structure radiation efficiency is calculated. A small antenna element has an excellent end-fire radiation pattern in the desired frequency bands. The antenna shows three reconfigurable bands, 25.17, 26.75, and 27.64 GHz, and gain (2.77-4.4) dBi. The suggested antenna is well suitable for future fifth-generation (5G) networks because of its notable features of small overall size (9.8×13×0.787) mm3, wide bandwidth, and frequency reconfigurability.